The Problematic Of Siri Marriage On Women's Destination And Dignity Indonesian Positive Legal Perspective : (Law No. 1 Of 1974 Concerning Marriage) - Bagas Rio Adi S; Ahmad Junaidi; Busriyanti Busriyanti (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Apart from being regulated by Islamic law, in Indonesia marriage is also regulated by the state, as is the registration of marriages which is regulated by article 2 of Law No. 1 of 1974 concerning marriage. These regulations were not made without reason, but these regulations were made to ensure orderly marriages for the Islamic community in Indonesia. The practice of unregistered marriages is based on different reasons, whether due to economic factors, not wanting to have difficulties with marriage administration, and so on. The research method used in this work is normative legal research or what can also be called literature study with various data sources which are then analyzed in depth and presented descriptively. Until we reach a simple conclusion that according to positive state law, a wife is not considered a legal wife, because there is no authentic evidence, because in the Compilation of Islamic Law the truth about the existence of a marriage can only be proven by the existence of a